Do Word of Mouth and Religiosity Affect the Interest of MSME Actors in Sharia P2P Lending? - Syihabudin Syihabudin; Najmudin Najmudin; Ma'zumi Ma'zumi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine (1). The influence of religiosity on the interest of MSME actors in Sharia peer to peer lending, (2). The influence of word of mouth on the interest of MSME actors in Sharia peer to peer lending, and (3). The influence of religiosity and word of mouth on the interest of MSME players in Sharia peer to peer lending. The object of this research is the SMEs in Banten province. The research method used is quantitative. Data collection techniques using a questionnaire in the form of a series or collection of questions that are arranged systematically in a list of questions, then sent to the respondent to be filled out. Questionnaires were distributed to 99 MSME actors in Banten Province. Data were analyzed using multiple linear regression methods through SPSS software version 23. The results of this study indicate that (1). Religiosity has a positive and significant effect on the interest of MSME actors in Sharia peer to peer lending. (2). Word of mouth has a negative and insignificant effect on the interest of MSME actors in sharia peer to peer lending, and (4). Word of mouth and religiosity have a positive and significant effect on the interest of MSME players in sharia peer to peer lending. The total contribution of the influence of religiosity, and Word of mouth on the interest in making loans at P2P Lending Syariah is 39.6 percent, while the rest is influenced by other variables not examined in this study.